Intermediate microeconomics and its application - Nicholson, Walter; Snyder, Christopher (Cengage Learning, 2015)
Offers an introduction to the economics of markets. This book focuses and includes relevant applications and strong examples as well as step-by-step video problems, an algebraic approach, and activities that allow you to learn by doing.